DIFFERENCES BETWEEN BRIDGE AND GANTRY CRANES’ DOWNTIMES - Spasojević-Brkić, Vesna K; Brkic, Aleksandar; Perisic, Martina; Misita, Mirjana; Janev, Nemanja (Journal of Applied Engineering Science, 2023)
Maintenance is especially crucial when it comes to construction machinery due its capacity to avoid or reduce the risk of serious accidents by recognizing probable failures and downtimes in a timely manner. To properly implement maintenance strategy, it is required to identify the existing linkages between downtime and failures that have already occurred first. This paper aims to analyze and compare data on the length of downtime, as well as the causes of downtime hazard levels on different bridge and gantry cranes. In order to ascertain whether there is a dependency between these two types of cranes, a comparison of the failure duration and hazard level between bridge and gantry cranes is done in this paper. In addition, a comparison of nine different types of bridge and gantry cranes were compared using the same comparation categories. After performing descriptive statistics and the Kolmogorov-Smirnov and Shapiro-Wilk normality tests, which revealed that the data did not follow a normal distribution, a comparison was done using the Mann-Whitney U test and the Kruskal-Wallis tests. All tests revealed no statisticaly significant differences in failure duration and hazard level within the tested categories, which opens up the possibility of applying the same risk management strategies and maintenance procedures regarding both examined crane types.
Keywords: cranes, downtimes, differences, statistics, equipment failures